Is there a relationship between hospital process digitalization and quality of care? Observational study using data from hospital quality report cards and the DigitalRadar Project - Justus Vogel; Alexander Haering; David Kuklinski; Alexander Geissler (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Hospital digitalization is to reduce costs, increase efficiency and productivity, and to improve quality of care. However, the literature lacks clarity on the meaning of "hospital digitalization," how to measure it, and what quality it might affect. We use data from the DigitalRadar project from 2021 describing - amongst other dimensions - process digitalization. We combine these statistically sensitive data with two process (pre-operative waiting time for osteosynthesis and hip replacement after femur fracture) and two risk-adjusted outcome quality indicators (inpatient mortality ratio of patients hospitalized with outpatient-acquired pneumonia, ratio of new cases with inpatient-acquired decubitus/ ulcers). We use multivariate linear regression with the respective quality indicator as dependent variable and different digitalization sub-dimensions as independent variables. Overall, we find no significant correlation between outcome or process quality and the majority of sub-dimensions. Only digitalization of documentation and diagnosis shows a consistently positive and weakly significant correlation with the ratio of new cases with a decubitus/ ulcer. We argue that this lack of statistical significance is in part due to the insufficient statistical sensitivity of the available quality indicators. Moreover, available and routinely measured quality indicators seem not to be apt to reflect digitalization effects. We conclude that empiric assessment of a digitalization-quality relationship needs the development of more fitting and sensitive quality indicators. Otherwise, study designs such as small-scale pre-post intervention assessments of the introduction of specific software will remain the gold standard in digitalization-quality research. – – Die Digitalisierung von Krankenhäusern hat das Potenzial, Kosten zu senken, die Effizienz zu steigern und die Qualität der Pflege zu verbessern. In einer Studie wurde analysiert, was unter 'Krankenhausdigitalisierung' zu verstehen ist, wie man sie messen kann und welche Auswirkungen sie auf die Qualität haben könnte. Dabei wurden Daten aus dem DigitalRadar-Projekt von 2021 verwendet, die unter anderem die Digitalisierung von Prozessen beschreiben. Diese Daten wurden mit verschiedenen Qualitätsindikatoren kombiniert, wie beispielsweise der präoperativen Wartezeit und der Sterblichkeitsrate von Patienten. Es wurden multivariate lineare Regressionen durchgeführt, um den Zusammenhang zwischen Digitalisierung und Qualität zu untersuchen. Insgesamt zeigte sich jedoch kein signifikanter Zusammenhang zwischen Digitalisierung und Qualität. Lediglich die Digitalisierung von Dokumentation und Diagnose zeigte eine schwach signifikante Korrelation mit dem Auftreten von Dekubitus und Ulcus-Fällen. Die mangelnde statistische Signifikanz könnte teilweise auf die unzureichende Sensitivität der verwendeten Qualitätsindikatoren zurückzuführen sein. Zudem scheinen die vorhandenen Qualitätsindikatoren nicht ausreichend zu sein, um die Auswirkungen der Digitalisierung auf die Qualität umfassend zu erfassen.
Keywords: I11; I18; M15; 330; Digitalization; quality of care; digitalization-quality relationship; hospital process digitalization